Design Methodology for Rehabilitation Robots: Application in an Exoskeleton for Upper Limb Rehabilitation - Giorgio Mackenzie Cruz Martínez; L. A. Z.-Avilés (Applied Sciences, 2020)
This article presents a methodology for the design of rehabilitation devices that considers factors involved in a clinical environment. This methodology integrates different disciplines that work together. The methodology is composed by three phases and 13 stages with specific tasks, the first phase includes the clinical context considering the requirements of the patient and therapist during the rehabilitation, the second phase is focused in engineering based on the philosophy of digital twin, and in the third phase is evaluated the device. This article explains the characteristics of the methodology and how it was applied in the design of an exoskeleton for passive rehabilitation of upper limb.